2021
DOI: 10.3390/nu13124475
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Metabolic Syndrome among Adults in China from 2015 to 2017

Abstract: The prevalence and influencing factors of metabolic syndrome (MetS) in Chinese residents aged 20 or older were investigated. The data were collected from China Nutrition and Health Surveillance (2015–2017), which used a stratified, multistage, random sampling method. A total of 130,018 residents aged 20 years or older from 31 provinces were included in this study. The National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP III) criteria were used to define MetS. The standardised prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
4
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 27 publications
(26 reference statements)
8
77
4
6
Order By: Relevance
“…(10) Smoke was divided into current smokers and non-smokers (including never smoked and already quit smoke). (11) Excessive alcohol drinking was divided into yes (equivalent to daily pure alcohol consumption over 25 g for males and 15 g for females) and no (for others) [ 46 ]. (12) Secondhand smoking was divided into yes (usually, being exposed to secondhand smoke more than half a week) and no (for others).…”
Section: Methodsmentioning
confidence: 99%
“…(10) Smoke was divided into current smokers and non-smokers (including never smoked and already quit smoke). (11) Excessive alcohol drinking was divided into yes (equivalent to daily pure alcohol consumption over 25 g for males and 15 g for females) and no (for others) [ 46 ]. (12) Secondhand smoking was divided into yes (usually, being exposed to secondhand smoke more than half a week) and no (for others).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic syndrome is a worldwide medical and public health concern [ 1 , 2 ]. It is a cluster of cardiovascular risk factors, not limited to increased waist circumference (WC), high systolic blood pressure (SBP) or diastolic blood pressure (DBP), high triglyceride (TG) levels, low high-density lipoprotein cholesterol (HDL-C), and elevated fasting blood glucose (FBG) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that global prevalence of metabolic syndrome is about 25% [ 5 ]. The prevalence of metabolic syndrome was 8.8% in 1991–1995, 29.3% in 2011–2015, and 31.1% in 2015–2017 in China [ 2 , 6 ]. It is associated with negative outcomes, including a high risk with type 2 diabetes, cardiovascular disease, and all-cause mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 The prevalence of MetS has been consistently increasing due to the global increase in the consumption of high caloric food and sedentary habits, especially in Asian populations where the standardized prevalence of MetS is as high as 31.1%. 2,4,5 MetS is considered a risk factor for cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Moreover, several studies also demonstrated that MetS was associated with liver fibrosis progression and liver cancer among patients with or without CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disorders are the main characteristic of metabolic syndrome (MetS), which is a clustering of obesity (particularly central adiposity), raised blood pressure, dysglycemia, elevated triglyceride levels, and low high‐density lipoprotein (HDL) cholesterol levels 3 . The prevalence of MetS has been consistently increasing due to the global increase in the consumption of high caloric food and sedentary habits, especially in Asian populations where the standardized prevalence of MetS is as high as 31.1% 2,4,5 . MetS is considered a risk factor for cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%